Expectations and Aspirations : A New Framework for Education in the Middle East and North Africa - El-Kogali, Safaa El Tayeb; Krafft, Caroline (Washington, DC: World Bank, 2018)
Education has a large untapped potential to contribute to human capital, well-being, and wealth in the Middle East and North Africa (MENA). It had been at the heart of the region’s history and civilizations for centuries. The region invested heavily in education for decades but has not been able to reap the benefits of its investments. Despite series of reforms, the region remained stuck in a low learning – low skills level. There are four key sets of tensions that are holding back education in the MENA region. These tensions: Credentials and skills, discipline and inquiry, control and autonomy, and tradition and modernity are shaped by society and are reflected in schools and classrooms. If not addressed, MENA will continue to operate below its potential.